Penggunaan Lagu untuk Meningkatkan Pelafalan Bahasa Inggris Siswa Kelas XI di SMA Negeri 2 Luwuk - Desrin Lebagi; Nurhaida Lakuana; Desriani Nggolaon (Jurnal Kreatif Online, 2022)
This research aimed to discover whether western songs improve students’ English pronunciation at the eleventh-grade students of SMA Negeri 2 Luwuk. It utilized quasi-experimental design. The population was the XI MIPA students of SMA Negeri 2 Luwuk which consisted of 58 students. The sampling used was purposive sampling. The sample was divided into two classes. Class XI MIPA 2 served as the experimental class and class XI MIPA 3 served as the control class, each class consisted of 17 students. The data were gathered through pronunciation test that included pre-test and post-test. In experimental class, the mean score of pre-test was 40.00 and post-test was 61.17. In control class, the mean score of pre-test was 27.05 and post-test was 44.70. The result of non-parametric by using Mann-Whitney U test showed that the             Sig.2-tailed or P value is 0.000 that is less than 0.05. It can be inferred that there is significant difference or H1 was accepted and H0 was rejected. It verified that songs can improve students’ pronunciation in English.